Managing Change: the people side of implementing CRM processes - Hann, David (2006)
This report has been produced with the remit of analysing the people side of change management with regard to a Customer Relationship Management (CRM) process implementation at Jupiter Design (Jupiter). An increasing churn of clients and 12- years of growth has made Jupiter realise they must maximise revenues from existing clients. The adoption of a CRM approach has been suggested as a possible solution.